Innsbruck Teleportation Experiment in the Wigner Formalism: A Realistic Description Based on the Role of the Zero-Point Field - Casado, Alberto; Guerra, Santiago; Plácido, José (Frontiers in Physics, 2020)
In this article, an undulatory description of the Innsbruck teleportation experiment is given, grounded in the role of the zero-point field (ZPF). The Wigner approach in the Heisenberg picture is used, so that the quadruple correlations of the field, along with the subtraction of the zero-point intensity at the detectors, are shown to be the essential ingredients that replace entanglement and collapse. This study contrasts sharply with the standard particle-like analysis and offers the possibility of understanding the hidden mechanism of teleportation, relying on vacuum amplitudes as hidden variables.